A new multi-element beta titanium alloy with a high yield strength exhibiting transformation and twinning induced plasticity effects. (1st March 2018) - Sadeghpour, S.; Abbasi, S.M.; Morakabati, M.; Kisko, A.; Karjalainen, L.P.; Porter, D.A.
Abstract: A new multi-element β titanium alloy Ti-3Al-5Mo-7V-3Cr (Ti-3573) was designed using the d-electron method based on a commercial alloy. An excellent yield strength of 750 MPa, and a high strain hardening rate (SHR) of 1800 MPa as well as 19% uniform elongation are some of the formidable mechanical characteristics exhibited by the designed alloy. Microstructural evaluation suggested that simultaneous transformation and twinning induced plasticity is responsible for the enhanced tensile properties. The results show that with precisely controlled alloying, it is possible to increase the yield strength with solid solutioning and still keep the SHR and ductility high enough. Graphical abstract: